WANPRESTASI DALAM PERJANJIAN ASURANSI KEBAKARAN: STUDI KASUS PUTUSAN MAHKAMAH AGUNG-RI NOMOR: 911 K/Pdt/2009 - ANDY WIRAWAN SALIM (PREMISE LAW JURNAL, 2016)
Insurance business has long existed in the Indonesian economy and participated in the national history, along with the other economic activities. However, it does not guarantee that it runs smoothly. Legal problem like default case of default in the fire insurance between PT. Pupuk Subur Makmur and PT. Asuransi Wahana Tata. The conclusion of the research was that PT. Pupuk Subur Makmur had been inattentive in carrying out its obligation by declaring default to PT. Pupuk Subur Makmur. In consequence, it had to be fined as it was decided by the Panel of Judges of the Supreme Court No. 911K/Pdt/ 2009. It is recommended that both parties have sense of justice in carrying out their right and obligation in the insurance contract, they have to be honest in order to avoid dispute in making an insurance contract between the guarantor and the insured. Keywords : Fire Insurance, Default, Supreme Court